2015
DOI: 10.1186/s12885-015-1019-1
|View full text |Cite
|
Sign up to set email alerts
|

MET FISH-positive status predicts short progression-free survival and overall survival after gefitinib treatment in lung adenocarcinoma with EGFR mutation

Abstract: BackgroundLung adenocarcinoma patients with EGFR gene mutations have shown a dramatic response to gefitinib. However, drug resistance eventually emerges which limits the mean duration of response. With that in view, we examined the correlations between MET gene status as assessed by fluorescence in situ hybridization (FISH) with overall survival (OS) and progression-free survival (PFS) in adenocarcinoma patients with EGFR gene mutations who had received gefitinib therapy.MethodsWe evaluated 35 lung cancer samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 22 publications
1
25
1
Order By: Relevance
“…This indicates that the tivantinib/erlotinib combination presents superior efficacy in EGFR-resistant patients with high expression of c-Met high or HGF high, both reported as poor prognostic factors. [8][9][10][11] Interestingly, similar superior efficacy in a poor prognosis population (ie, c-Met high and/or HGF high) was observed in previous phase III studies testing the tivantinib/erlotinib combination, even though those studies enrolled patients with NSCLC with backgrounds different from this study. The MARQUEE study enrolled EGFR-TKI-naive Caucasian patients including about 10% EGFR mutation-positive patients, and resulted in longer OS in c-Met high; HR was 0.70 (95% CI 0.49 to 1.01, vs placebo) in c-Met high, and 0.90 (95% CI 0.64 to 1.26, vs placebo) in c-Met low.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This indicates that the tivantinib/erlotinib combination presents superior efficacy in EGFR-resistant patients with high expression of c-Met high or HGF high, both reported as poor prognostic factors. [8][9][10][11] Interestingly, similar superior efficacy in a poor prognosis population (ie, c-Met high and/or HGF high) was observed in previous phase III studies testing the tivantinib/erlotinib combination, even though those studies enrolled patients with NSCLC with backgrounds different from this study. The MARQUEE study enrolled EGFR-TKI-naive Caucasian patients including about 10% EGFR mutation-positive patients, and resulted in longer OS in c-Met high; HR was 0.70 (95% CI 0.49 to 1.01, vs placebo) in c-Met high, and 0.90 (95% CI 0.64 to 1.26, vs placebo) in c-Met low.…”
Section: Discussionsupporting
confidence: 75%
“…7 Activation of HGF/c-Met signalling due to overexpression of HGF/c-Met is reported to be involved in tumour infiltration and metastasis, and is identified as a poor prognosis factor in NSCLC. [8][9][10][11] Tivantinib (ARQ 197) is an oral, non-ATP-competitive, low-molecular weight selective c-Met inhibitor. The primary metabolic enzyme of tivantinib, CYP2C19, is known for the gene polymorphism associated with loss of function.…”
Section: Introductionmentioning
confidence: 99%
“…In lung cancer, MET can be activated by HGF stimulation (11). Our recent study demonstrated that MET amplification and gene copy number gains showed a short response to gefitinib treatments in lung adenocarcinoma with EGFR mutation (12). Recently, MET inhibitors have been administered to NSCLC patients who are na€ ve or resistant to EGFR TKIs in a clinical trial (13).…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation of ABCB1, CD44 and ALDH1A1 protein expression. IHC scoring was performed using the Histoscore (H-score) (12,13). CD44 expression level was scored on a scale according to a previous study as follows: No expression, 0; low expression, 1+; and high expression, 2+ and 3+ (14).…”
Section: Methodsmentioning
confidence: 99%